(3YfhGf GdTQa GdhGaj aj Gdabg hGdfMh hGdYQhV hGdbhGais - (3TQa GdOjf ESeGYjd Hf CHj HcQ Hf YHO Gddg Hf EHQGgje GdebQj GdTQLj GdMSjfj, GdTGhQj GdRHjOj Gdjefj,J (B837 (3g` s ((3CMeO Hf UdGM Hf CMeO GdeNdGai s)
(3ChdgG (B:s
(3GdMeO ddg hdi GdMeO hHYO agPG cJGH Ldjd , cJHJg hde CSHb HYO Edjg , CdaJg eNJUQkG ai Gdabg s
(3BNQgG (B:s
(3aGSJdMb Ydi hMOg CNGce jKHJ , hEf eGJ eMeO hYdi MGFR EQjKg dRe GdfSH hUdi Gddg Ydi eMeO hBdg hSde Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B23 - (3U(B181s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bGHdgG YHO GdhGMO Hf eMeO Gdedjci SfI (B1017(3g` s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs